The fault-tolerant consensus strategy for leaderless Multi-AUV system on heterogeneous condensation topology. (1st February 2022) - Lin, Xiaogong; Tian, Weida; Zhang, Wei; Li, Zixuan; Zhang, Chao
Abstract: The present paper proposes a distributed fault-tolerant consensus control protocol strategy for leaderless multi-autonomous underwater vehicle (AUV) systems, where actuators have a partial break-down. Instead of the global information, this strategy applies the relative state of the topology. Also, the topology graph can be any heterogeneous condensation digraph with a spanning tree in the communication network. The linear feedback technique is used to linearize the system model into a second-order multi-AUV system. Then, the Lyapunov functional method is used to prove the system's stability and astringency and the algorithm's effectiveness is simulated numerically. It was found that the actuator efficiency could not be the same in each AUV. Also, the partial actuator loss of effectiveness faults is more typical and complicated. In addition, each AUV's state can converge to the same asymptote, and the consensus error can converge to zero. Highlights: A Fault-tolerant consensus control (FTCC) strategy of a multi-AUV system is proposed. FTCC strategy for leaderless multi-AUV systems on the heterogeneous condensation topology. A fault-tolerant consensus of multi-AUV stability criteria is established. A simulation example of the multi-AUV system with partial actuator loss of effectiveness is performed. The leaderless multi-AUV FTCC protocol applies the topology graph's relative state instead of the global.